Lymphovascular invasion as a negative prognostic factor for triple-negative breast cancer after surgery - Ahn, Ki Jung; Park, Jisun; Choi, Yunseon (Radiation oncology journal, 2017)
This study aimed to evaluate the prognostic effects of lymphovascular invasion (LVI) in triple-negative breast cancer (TNBC) patients who underwent surgical resection. A total of 63 non-metastatic TNBC patients who underwent surgical resection were retrospectively investigated from 2007 to 2016 in Inje University Busan Paik Hospital. Pathological tests revealed that 12 patients (19.0%) had LVI. Approximately 61.9% (n = 39) of the patients' samples stained positive for p53. Additional chemotherapy and radiotherapy (RT) were performed in 53 (84.1%) and 47 (74.6%) patients, respectively. The median follow-up period was 39.5 months (range, 5.9 to 123.0 months). The pathological T stage (p = 0.008), N stage (p = 0.014), and p53 positivity (p = 0.044) were associated with LVI. Overall, the 3-year disease-free survival (DFS) rate and overall survival (OS) rate were 85.4% and 90.2%, respectively. Ten patients (15.9%) experienced relapse. LVI (n = 12) was associated with relapses (p = 0.016). p53 positivity was correlated with poor DFS (p = 0.048). Furthermore, LVI was related to poor DFS (p = 0.011) and OS (p = 0.001) and considered as an independent prognostic factor for DFS (p = 0.039). The 3-year DFS of patients with LVI (n = 12) was only 58.3%. Adjuvant RT minimized the negative prognostic effect of LVI on DFS (p = 0.068 [with RT] vs. p = 0.011 [without RT]). LVI was related to the detrimental effects of disease progression and survival of TNBC patients. Thus, a more effective treatment strategy is needed for TNBC patients with LVI.